Polycyclic aromatic hydrocarbon metabolites and 7-ethoxyresorufin O-deethylase activity in caged European eels. - Fenet, Hélène; Gomez, Elena; Rosain, D.; Casellas, Claude (Archives of Environmental Contamination and Toxicology, 2006)
International audience This study investigated the contribution of two biomarkers, bile polycyclic aromatic hydrocarbon (PAH) metabolites and 7-ethoxyresorufin O-deethylase (EROD), activity in the assessment of PAH contaminated sites. European eels (Anguilla anguilla) were caged in a freshwater stream upstream and downstream from local industrial effluent outlets. Bile PAH metabolites were recorded as fluorescent aromatic compounds by synchronous fluorescence spectroscopy and as a marker for total PAH metabolism: 1-hydroxypyrene (1-OH Pyr) was isolated by high-pressure liquid chromatography and quantified. After 14 and 28 days of caging, EROD activity, bile fluorescence (synchronous fluorometric measurement), and 1-OH Pyr concentrations in bile were higher at the downstream site than at the upstream site. This increase was similar after 2 and 4 weeks of caging. During a reversibility study, EROD activity, bile fluorescence, and 1-OH Pyr concentrations decreased, and this trend was similar for the three markers. These results suggest that PAHs could be the main factor responsible for EROD induction in eels caged at the downstream site.